A Roadmap for Fixing the Heart: RNA Regulatory Networks in Cardiac Disease - Rong Tang; Tianxin Long; Kathy O. Lui; Yili Chen; Zhan-Peng Huang (Elsevier, 2020)
With the continuous development of RNA biology and massive genome-wide transcriptome analysis, more and more RNA molecules and their functions have been explored in the last decade. Increasing evidence has demonstrated that RNA-related regulatory networks play an important role in a variety of human diseases, including cardiovascular diseases. In this review, we focus on RNA regulatory networks in heart disease, most of which are devastating conditions with no known cure. We systemically summarize recent discoveries of important new components of RNA regulatory networks, including microRNAs, long non-coding RNAs, and circular RNAs, as well as multiple regulators that affect the activity of these networks in cardiac physiology and pathology. In addition, this review covers emerging micropeptides, which represent short open reading frames (sORFs) in long non-coding RNA transcripts that may modulate cardiac physiology. Based on the current knowledge of RNA regulatory networks, we think that ongoing discoveries will not only provide us a better understanding of the molecular mechanisms that underlie heart disease, but will also identify novel biomarkers and therapeutic targets for the diagnosis and treatment of cardiac disease.